Steinbeck Newsday interview
John Steinbeck in the interview with Newsday's Val Duncan. For a photocopy, see MLA files under Duncan, Val. 'A Nobel Author Views His Life, Times: Steinbeck's Greatest Creation: Faith in Himself.'